Protective Role of Peroxisome Proliferator–Activated Receptor-γ in the Development of Intracranial Aneurysm Rupture. Issue 6 (June 2015) - Shimada, Kenji; Furukawa, Hajime; Wada, Kosuke; Korai, Masaaki; Wei, Yuan; Tada, Yoshiteru; Kuwabara, Atsushi; Shikata, Fumiaki; Kitazato, Keiko T.; Nagahiro, Shinji; Lawton, Michael T.; Hashimoto, Tomoki
Abstract : Background and Purpose—: Inflammation is emerging as a key component of the pathophysiology of intracranial aneurysms. Peroxisome proliferator–activated receptor-γ (PPARγ) is a nuclear hormone receptor of which activation modulates various aspects of inflammation. Methods—: Using a mouse model of intracranial aneurysm, we examined the potential roles of PPARγ in the development of rupture of intracranial aneurysm. Results—: A PPARγ agonist, pioglitazone, significantly reduced the incidence of ruptured aneurysms and the rupture rate without affecting the total incidence aneurysm (unruptured aneurysms and ruptured aneurysms). PPARγ antagonist (GW9662) abolished the protective effect of pioglitazone. The protective effect of pioglitazone was absent in mice lacking macrophage PPARγ. Pioglitazone treatment reduced the mRNA levels of inflammatory cytokines (monocyte chemoattractant factor-1, interleukin-1, and interleukin-6) that are primarily produced by macrophages in the cerebral arteries. Pioglitazone treatment reduced the infiltration of M1 macrophage into the cerebral arteries and the macrophage M1/M2 ratio. Depletion of macrophages significantly reduced the rupture rate. Conclusions—: Our data showed that the activation of macrophage PPARγ protects against the development of aneurysmal rupture. PPARγ in inflammatory cells may be a potential therapeutic target for the prevention of aneurysmal rupture. Abstract : Supplemental Digital Content is available in the text.